Optimizing Literacy Skills in Reading and Writing Al-Qur'an through the Development of Islamic Religious Education Learning Modules - Rahma, Nelli Dwi; Nurhikmah, Nurhikmah; Zainuddin, Fauziah; Muhaemin, Muhaemin (South Sulawesi Education Development (SSED), 2024)
Study This title development of the Internal Islamic Religious Education Learning Module Increase Ability Literacy Reading and Writing the Koran at SMA Negeri 3 Palopo. Study This aims to know the Design, Validity, Practicality, and Effectiveness of digital-based modules on the eye Islamic Religious Education lessons at SMAN 3 Palopo. Study This uses type R&D (Research and Development) research with the ADDIE (Analysis et al., Evaluation) development model. Research results show that the Islamic Religious Education module from facet validity has fulfilled valid criteria with an acquisition score of 84.3% by expert design, 95% by media experts, 94.2% by specialist material, and 88.5% by expert Language. Fulfill criteria practical with acquisition scores of 84% by educators and 92% by participants. The digital-based Reading and Writing Al-Qur'an module is also effective in learning Because it has obtained completeness classical 86% test choice double. Therefore, the Islamic Religious Education module in the Reading and Writing Al-Qur'an sub-material is appropriate for the learning process.